2018
DOI: 10.2105/ajph.2018.304684
|View full text |Cite
|
Sign up to set email alerts
|

The 20 Most Important and Most Preventable Health Problems of China: A Delphi Consultation of Chinese Experts

Abstract: Objectives. To identify the 20 most important and most preventable health problems that should be addressed in the next 20 years in China. Methods. In 2015, we applied a modified electronic Delphi technique to reach consensus from a panel of top Chinese health experts (n = 70), who were requested to identify 20 health problems that, in their judgment, were most important and preventable. We also compared the results with evidences from epidemiological studies on disease-specific mortalities and disability-adj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…We will modify the list of question items, including those regarded as the most important (9 points) by at least 10% of panellists in the first round. 24 A summary table of the results, including group ratings and comments obtained from round 1, will be prepared. This table is used to provide controlled feedback and statistical group responses to participants.…”
Section: Data Collectionmentioning
confidence: 99%
“…We will modify the list of question items, including those regarded as the most important (9 points) by at least 10% of panellists in the first round. 24 A summary table of the results, including group ratings and comments obtained from round 1, will be prepared. This table is used to provide controlled feedback and statistical group responses to participants.…”
Section: Data Collectionmentioning
confidence: 99%
“…Hepatitis is viewed by Chinese experts as one of the 20 most important and most preventable health problems of China. 1 Hepatitis B virus (HBV), as the most common cause of hepatitis worldwide, accounts for at least 50% cases of hepatocellular carcinoma. Currently, although preventable with safe and effective vaccines, there is still about 3% of the global population chronically infected with HBV.…”
Section: Introductionmentioning
confidence: 99%
“…It is also viewed as one of the 20 most important and most preventable health problems of China. 1 This disease is prevalent in chronic HBV-infected patients, partly because it is one of the adverse effects of interferon given against HBV. 4 Previous studies reported that HBVinfected patients had significantly higher levels of depression compared to healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the overall prevalence of diabetes among Chinese adults was 11.2% according to a nationally representative cross-sectional survey conducted in 2015 to 2017 [3]. Type 2 diabetes mellitus (T2DM), which accounts for more than 90% of the person with diabetes, has been recognized as one of the most preventable diseases over the next two decades [4].…”
Section: Introductionmentioning
confidence: 99%